Nonhuman Agencies in the Twenty-First-Century Anglophone Novel - Liebermann, Yvonne,Rahn, Judith,Burger, Bettina (Springer International Publishing AG, 2021)
Intro – Preface: About the Book – Acknowledgements – Contents – Notes on Contributors – List of Figures – Introduction: Narrating the Nonhuman – Approaches to the Nonhuman – The Nonhuman and the Novel Form – Chapter Overview – References – Section I: Nonhuman Poetics: Agency of Literary Forms – Forms of Agency, Agency of Forms: Reading and Teaching More-Than-Human Fictions – Introduction: Making Words Matter – From Representations to Entanglement – Rooting Intertextual Agencies in Sigrid Nunez's The Friend (2018) – Teaching More-Than-Human Intertextual Relationality – References – Nonhuman Agencies in and of Literature: Yvonne Adhiambo Owuor's The Dragonfly Sea – Introduction – The Agency of Matter and Flat Ontologies – Nonhuman Agencies in and of Literature – More-Than-Human-Worlds in The Dragonfly Sea: Oceanic Cartographies – Multispecies Interdependencies – Reading with the Ocean – References – Deontologising the Nonhuman: Arthur Gordon Pym, Contemporary Literature, and the Limits of the Human – Introduction: The Nonhuman at Peak Humanity – The Nonhuman in Theory: Three Snapshots – Literature at the Limits of the Human: The Afterlives of Arthur Gordon Pym – Conclusion: Literature and the Dynamics of De-/Re-/In-/Non-/ …-humanisation – References – Section II: Negotiating the Human in the Light of the Nonhuman – Anthropogenesis: Ian McEwan's Fictions of the Human – Introduction – The Human and Its Others – Literary Fiction as Anthropology – Encapsulating the Human: Nutshell – Problems of Scale: Solar – Human Technology: Machines Like Me – Conclusion – References – Arctic Snowmobilities: Encounters with Sled Dogs in Gary Paulsen's Winterdance – Introduction – Moving with Sled Dogs – Moving in/on Snow: Mapping Arctic Space – Human: Nonhuman Encounters-Moving Between Identity Positions – Conclusion.
Description based on publisher supplied metadata and other sources
Keywords: Literature; Modern-20th century; Literature; Modern-21st century; Literature-Philosophy; Electronic books